Penggunaan Mind Mapping Berbantuan Media LCD untuk Meningkatkan Keaktifan dan Hasil Belajar PKn Siswa Kelas IV SD Negeri Purwosari - Sricahyanti, Nurini (Paedagogie, 2018)
The objective of this sutudy is to improve the students’ activeness and achievement of Civic Education by the use of LCD-aided mind mapping. It is a classroom action research with 2 cycles. It was conducted in the first semester of Academic Year 2016/2017, involving 35 students. The results show that in pre-cycle the number of those who pass the standard score (KKM) were 10 (28.57%), and increased in cycle I meeting 1 to 11 (31.14%), 15 students (42.85%) in cycle I meeting 2, 27 students (77.15%) in cycle II meeting 1, and finally 30 students (85.70%) in cycle II meeting 2. The average score increased from 59.43, 60.57, 67.57, then 75.86. The percentage of the students’ activeness increased from 37.14% in cycle I to 100%in cycle II. It indicates that the use of LCD-aided mind mapping can improve the students’ activeness and achievement of Civic Education.